Autonomy as the Result of Relations: Role of Attachment to Mother and Peers in Volunteering Motivation in Adolescents - S.V. Molchanov; O.V. Almazova; N.N. Poskrebysheva (Moscow State University of Psychology and Education, 2022)
The relevance of the study is defined by the role of volunteering as social practice in developing adolescents' autonomy. Volunteering attitudes in adolescents are considered a meaningful indicator of personal autonomy development. The purpose of the study is to identify the features of volunteering motivation in adolescents as a manifestation of personal autonomy. The research tasks included the following: studying the volunteering motivation of adolescents with and without experience in volunteering; identifying the relationship between the volunteering motivation of adolescents and the type of attachment to mother; revealing the connection between the volunteering motivation and the features of adolescents' relationships with their peers. The following techniques were used: volunteering motivation questionnaire; mother and peer attachment type questionnaires. The sample consisted of 329 subjects aged 14 to 18 years. The study revealed the relationship between the mother attachment type and the attitude to volunteering in adolescents. Positive relationships with peers, including satisfaction with communication, trust and secure attachment, are associated with high willingness of adolescents to participate in volunteer activities as an indicator of personal autonomy.